β-Blocker use is not associated with improved clinical outcomes in women with breast cancer: a meta-analysis - Li, Chaoran (Biosci Rep, 2020)
Background: Evidence remains inconsistent regarding the potential influence of β-blocker (BB) use on clinical outcomes in women with breast cancer. We aimed to evaluate the association between BB and prognosis of breast cancer in an updated meta-analysis. Methods: Follow-up studies comparing the clinical outcomes of breast cancer in women with and without use of BB were included by search of PubMed, Embase, and Cochrane’s Library. A random-effect model was used to pool the results. Results: Seventeen observational studies were included. Pooled results did not support a significant association between BB use and breast cancer recurrence (risk ratio [RR] = 0.85, 95% confidence interval [CI]: 0.68–1.07, P=0.17), breast cancer related deaths (RR = 0.83, 95% CI: 0.65–1.06, P=0.14), or all-cause deaths (RR = 1.01, 95% CI: 0.91–1.11, P=0.91) in women with breast cancer. Study characteristics such as sample size, definition of BB use, follow-up durations, adjustment of menopausal status, or quality score did not significantly affect the results. Subgroup analyses showed that BB may be associated with a trend of reduced risk of all-cause deaths in women with breast cancer in prospective studies (two datasets, RR = 0.81, P=0.05), but not in retrospective studies (eight datasets, RR = 1.06, P=0.16; P for subgroup analyses = 0.02). Conclusions: Current evidence from observational studies does not support a significant association between BB use and improved prognosis in women with breast cancer.